Optimising brine regeneration of ion-exchange resins: effects of pre-treatment temperature, brine concentration, and ratio - Shin-Yong Yeoh; Kher-Wei Lai; Swee-Yong Pung; Kun-Yi Andrew Lin; Akihiko Matsumoto; Fei-Yee Yeoh (Clean Technologies and Environmental Policy, 2026)
Ion exchange resins (IERs) are widely used in water treatment to remove hardness ions such as calcium (Ca 2+ ) and magnesium (Mg 2+ ), but their long-term performance is constrained by fouling, inefficient regeneration, and high chemical consumption. This study systematically optimised brine-based regeneration by evaluating four key operational parameters: pre-treatment mode (swollen vs dried), resin-to-brine ratio (1:1–1:4), brining temperature (25–60 °C), and NaCl concentration (1%, 5%, 10%). Dried resin exhibited approximately 14% shrinkage compared to the swollen state and achieved superior hardness removal due to reduced pore size and shortened diffusion pathways. SEM analysis confirmed structural damage and microbial fouling, underscoring the importance of pre-treatment. The optimal condition, dried resin regenerated with 5% NaCl at a 1:1 resin:brine ratio and 55 °C, yielded the highest Ca 2+ and Mg 2+ removal, as verified by atomic absorption spectrometry and oxidation–reduction potential analysis. This optimised strategy enhances regeneration efficiency, lowers chemical demand, minimises brine waste, and extends resin service life. The findings provide a cost-effective and sustainable approach for high-purity water production, with strong relevance to industries such as pharmaceuticals, food and beverage, and power generation. Graphical Abstract

Microbial food safety assessment of dried edible mushrooms - Ana Hazirah Ajis; Lin June Chong; Yee Shin Tan; Lay Ching Chai (Journal of Consumer Protection and Food Safety, 2017)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)